VOLTAGE AND FREQUENCY BASED ISLANDING DETECTION FOR GRID CONNECTED SOLAR PV SYSTEM - Saipolyazan, Amir Hakim (2018)
This paper offer a research experiment of passive detection method based on variation of two parameters at point common coupling (PCC) which are voltage and frequency during pre-islanding and islanding. THD of voltage and current parameters are analyzed to identify the impact towards islanding detection method. Islanding is detected by considering three type of variation parameters which are increment percentage, depreciation percentage and rate of change for all parameters mentioned above within two seconds. The main objective of this project is to implement passive detection method using voltage and frequency parameters at Point Common Coupling (PCC) as variable parameters. In this project, PCC is defined as node between output of solar inverter and the grid supply. Those parameters will be analyzed at PCC during islanding. Throughout this research, the output voltage and frequency ay the inverter are analyzed to identify the effectiveness of passive detection method. In addition, the objective of this research is to identify the impact of total harmonic distortion (THD) of voltage and current parameters using passive detection method. Next, the research methodology will have five different phases to achieve the objectives where in early stage it required to identify different parameters to be using in passive detection method. Next, this research required to develop experiment method by determine circuit configuration to integrate between solar inverter with power grid. In 3rd & 4th phase, the data were collected and validated by comparing the trends with other experiment finding. In final steps, all the data were analyzed and interpret by calculating the rate of change and percentage of depreciation and increment. For the result, voltage variation during islanding show a significant of result. However, along the experiment, frequency result didn’t show any significant of trend to analyze the islanding in 2 seconds of period. Therefore, total harmonic distortion (THD) of voltage and current is analyzed if both parameters could give impact to islanding detection method using passive detection method. Based on the result, the THD of voltage and current trends showed a significant trend of data to identify the islanding. In this experiment, the variation of all parameters during islanding are calculated by using increment percentage, decrement percentage and rate of change in specific period of change. Through these parameters, the trends indicate to detect islanding phenomena.